Nanotechnology: a new regime for the public in science? (Scientiae Studia, 2012)
"Public engagement in science" is one of the buzzwords that, since 2000, has been used in nanotechnology programs. To what extent does public engagement disrupt the traditional relations between science and the public? This paper briefly contrasts the traditional model of science communication - the diffusionist model - that prevailed in the twentieth century and the new model - the participatory model - that tends to prevail nowadays. Then it will try to disentangle the assumptions underlying the public dialogue initiated about nanotechnology, and conclude that nanotechnology actually develops a managerial model of society.